Az állami támogatás hatása a projektfinanszírozásra erkölcsi kockázat és pozitív externáliák mellett Szerződéselméleti megközelítés - Edina Berlinger; Anita Lovas; Péter Juhász (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
– It is a highly disputed question in the literature how state subsidy influences the behavior of the entrepreneurs and accordingly the growth prospects of the economy. Most authors agree that state intervention in financing deteriorates the incentives of the entrepreneur, but there is no consensus whether its overall effect is positive or negative if we take into consideration the positive externalities of the projects too. Several authors investigate different subsidy forms (refundable/nonrefundable, prior/posterior, conditional/unconditional) searching for the optimal one(s). In this article we show in the framework of a three-player model (entrepreneur, bank, state) that under moral hazard and positive externalities state subsidy creates value. Moreover, a well-designed subsidy scheme improves incentives and instead of crowding out it boosts private financing. However, in this model the concrete form of the state subsidy is totally irrelevant as all forms will lead exactly to the same welfare effect. The only exception is the prior subsidy to be refunded both in case of success and failure which has neither a positive nor a negative effect.
Keywords: D28; D86; G38; H23; H81; 330; state subsidy; moral hazard; externalities; contract theory